“I want to win in life”: International student-athletes’ postgraduate decisions to remain in the United States - Jolly , Karina; Corr, Chris; Stokowski, Sarah; Paule-Koba, Amanda L. (Journal of International Students, 2025)
While international students enroll in and matriculate through higher education in the United States for various reasons, no study to date has examined the postgraduate ambitions of international student-athletes concerning their intention to remain in the United States. Accordingly, the present study explored the decisions of former international student-athletes to remain in the U.S. after graduation. The findings revealed that opportunities, influences, and perseverance were the main research priorities for international student-athletes in the U.S. Although international student-athletes most often indicate sports and athletics opportunities as the primary motivation for attending college in the United States, international student-athletes desired career, opportunities, and support from families and friends upon the conclusion of their athletic career factors in their decision to remain in the United States postgraduation.